2007
DOI: 10.1002/dvdy.21293
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial regulation of bone morphogenetic protein signaling in late lung development

Abstract: Bone morphogenetic proteins (BMPs) play important roles in early lung development. No study to date has addressed a role for BMP signaling in late lung development. We describe changes in the expression and localization of BMP receptors (Bmpr1a, Bmpr1b, and Bmpr2) and Smad (Smad1, Smad4, Smad5, and Smad8) intracellular signaling proteins during the saccular and alveolarization stages of late lung development. BMP signaling, assessed by Smad1/5 phosphorylation, nuclear translocation, and induction of id1, id2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The precise response of cells to Bmps likely depends on the level of ligand, the activity of other signaling pathways, and cell type. Bmps likely play additional roles in later lung development and postnatally (Alejandre-Alcázar et al, 2007). …”
Section: Figurementioning
confidence: 99%
“…The precise response of cells to Bmps likely depends on the level of ligand, the activity of other signaling pathways, and cell type. Bmps likely play additional roles in later lung development and postnatally (Alejandre-Alcázar et al, 2007). …”
Section: Figurementioning
confidence: 99%
“…An inhibitor of mTOR, rapamycin, is already used clinically as an immunosuppressant to prevent organ rejection after transplantation [14], [15]. In addition, the use of rapamycin in patients suffering from the destructive lung disease, lymphangioleiomyomatosis [16], has demonstrated promise in its ability to reduce disease symptoms and stabilize lung function [17]. Previously, our lab demonstrated that inhibition of mTOR with rapamycin prevented allergic asthma in a mouse model induced by exposure to the allergen, house dust mite (HDM).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that platelet derived growth factor (PDGF) and FGF signaling is crucial for myofibroblast differentiation and subsequent onset of secondary septation (24–29). WNT, BMP, and TGFβ signaling components have also been implicated to play a role in fibroblast differentiation during alveolarization (3032). Additionally, correct deposition of extracellular matrix (ECM) proteins by myofibroblasts, like elastin and collagen, plays a crucial role during secondary septation (33, 34).…”
Section: Introductionmentioning
confidence: 99%